The use of e-technology in operational processes of organisations in Polokwane Municipality - Ledwaba, N. F.; Pelser, G. P. J. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
The aim of this paper is to examine how organisations use e-technology in their operational processes to create value. E-technology is defined as the devices, mechanisms or networks such as internet, intranet and/or extranet which are utilised to create, assist, disseminate or facilitate personal, business, organisational and institutional action and information. The study was quantitative in nature. Exploratory and descriptive research was used to outline the use of e-technology in operational processes of organisations. A sample size of 50 businesses was utilised. The theoretical basis was used to develop the questionnaire and a pilot study was also conducted to enhance validity. To ascertain reliability of the research tool, the Cronbach alpha test was utilised. A self-administered questionnaire was utilised to collect data. Data analysis was done using SPSS. The results are a clear explication of the factors influencing the utilisation and impact of e-technology adoption in operational processes of organisations. Recommendations are made to adopt e-technology to enhance effectiveness and efficiency within their operational processes and also enable businesses to attain their organisational goals.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: E-technology; Operational processes; Performance measurement; Value proposition; Technology; Performance -- Measurement